Preparation of poly(ionic liquids)-functionalized polypyrrole nanotubes and their electrocatalytic application to simultaneously determine dopamine and ascorbic acid. Issue 26 (10th June 2015) - Mao, Hui; Zhang, Haifeng; Liang, Jiachen; Liu, Daliang; Wu, Shuyao; Zhang, Yu; Zhang, Yuyang; Wu, Qiuhua; Zhang, Guolin; Song, Xi-Ming
Abstract : Novel poly(ionic liquids)-functionalized polypyrrole nanotubes presented an excellent performance for simultaneous determination to DA and AA. Abstract : Novel poly(ionic liquids) functionalized polypyrrole nanotubes (PILs/PPyNTs) were successfully synthesized. 1-Vinyl-3-ethylimidazole bromide (VEIB) was polymerized on the surface of novel polymerizable vinyl imidazolium-type IL modified PPyNTs prepared by a covalent method. Due to the modification of PILs, the dispersibility of PILs/PPyNTs in aqueous solution was significantly improved and their surface charge properties were obviously changed to electropositivity. Because of the synergetic effects of conductive PPyNTs and biocompatible PILs, excellent electrochemical catalytic activities towards dopamine (DA) and ascorbic acid (AA) were achieved using a PILs/PPyNTs modified glassy carbon electrode (GCE), which gave a large potential difference enough to well distinguish DA from AA, with excellent sensitivity and good stability, for the simultaneous detection of DA and AA. The existence of PILs effectively improved the transmission mode of electrons of DA and AA oxidation on the electrode and resulted in their different electrocatalytic performance.